2002
DOI: 10.1097/00005392-200202000-00080
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vascular Endothelial Growth Factor on a Rat Model of Traumatic Arteriogenic Erectile Dysfunction

Abstract: Ligation of bilateral internal iliac arteries produced a reliable animal model of traumatic arteriogenic erectile dysfunction. Intracavernous injection of VEGF minutes after arterial ligation facilitated the recovery of erectile function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 31 publications
0
50
0
2
Order By: Relevance
“…Therefore, neovascularization has emerged as a strategy for treating vasculogenic ED and is anticipated to be more effective for patients with moderate to severe ED and to restore physiologic erections, i.e., spontaneity of the sexual act. Local intracavernous delivery of the vascular endothelial growth factor-A (VEGF-A) gene or protein has been shown to restore erectile function in animal models of vasculogenic ED7151617. However, treatment with exogenous VEGF-A often results in a pathologic angiogenesis producing leaky, inflamed, and disorganized blood vessels in experimental systems1819, greatly compromising its therapeutic value.…”
mentioning
confidence: 99%
“…Therefore, neovascularization has emerged as a strategy for treating vasculogenic ED and is anticipated to be more effective for patients with moderate to severe ED and to restore physiologic erections, i.e., spontaneity of the sexual act. Local intracavernous delivery of the vascular endothelial growth factor-A (VEGF-A) gene or protein has been shown to restore erectile function in animal models of vasculogenic ED7151617. However, treatment with exogenous VEGF-A often results in a pathologic angiogenesis producing leaky, inflamed, and disorganized blood vessels in experimental systems1819, greatly compromising its therapeutic value.…”
mentioning
confidence: 99%
“…Although no direct evidence, such as collateral circulation building or regrowth of new blood vessels, has demonstrated autocompensation occurred in the BIIAL, HFD and BCH groups at 12 weeks, the erectile function of these three groups decreased immediately after injuring according to previous report [12]. Indeed, our results indicate erectile function, such as ICP/MAP, nNOS and eNOS, in BIIAL and HFD groups are much better than that in BCH group, which hints that more erectile function is restored in BIIAL and HFD groups rather than that in BCH group, though the extent is modest, as well as Lee's work [12]. Future work concentrating on autocompensation at different time points would be expected to clarify the specific mechanism.…”
Section: Discussionmentioning
confidence: 71%
“…For example, Bakircioglu reported that 4 months were necessary to establish a hyperlipidemia-induced ED model in rats, and Metze had reported severe sexual dysfunction after major pelvic trauma [11], [21]. Lee successfully developed a traumatic arteriogenic ED rat model, but ED may occur only in the acute phase and erectile function may show autocompensation at 6 weeks after surgery [12], [16]. Although no direct evidence, such as collateral circulation building or regrowth of new blood vessels, has demonstrated autocompensation occurred in the BIIAL, HFD and BCH groups at 12 weeks, the erectile function of these three groups decreased immediately after injuring according to previous report [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [57] showed that intracorporeal administration of brain-derived neurotrophic factors after bilateral cavernous nerve cryoablation in rats prevents the degeneration of neural nitric oxide synthase containing neurons, with an enhancement of recovery of erectile function. In addition, the intracorporeal injection of vascular endothelial growth factor in rats with arteriogenic erectile dysfunction can provide a protective effect on erectile function.…”
Section: Growth Factors For Cavernous Nerve Regenerationmentioning
confidence: 99%